Knowledge and attitudes regarding HIV/AIDS and antiretroviral therapy among patients at a Nigerian treatment clinic - Samuel Anu Olowookere; Akinola Ayoola Fatiregun; Isaac F Adewole (Journal of Infection in Developing Countries)
Introduction:  We assessed the knowledge of and attitudes toward HIV/AIDS and antiretroviral therapy (ART) in people living with HIV/AIDS (PLWHA).